IMPLICATIONS AND CONTRIBUTIONS OF STUDENT COMMUNITY SERVICE PROGRAMS TO THE IMPROVEMENT OF EDUCATION, SOCIAL, ECONOMIC, ENVIRONMENTAL, AND RELIGIOUS EXPERIENCES IN AEK GAMBIR VILLAGE, LUMUT DISTRICT, CENTRAL TAPANULI REGENCY - Samosir, Hasrat Effendi; Lubis, Ahmad Rizal; Putri, S. Ritonga Ari; Matondang, Adelia Rizky; Azis, Khoirul (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The Community Service Program (Kuliah Kerja Nyata/KKN) implements the Tri Dharma of Higher Education in community service, improving rural life quality and providing students with social learning experiences. This study analyzes contributions of students from State Islamic University of North Sumatra through KKN in Aek Gambir Village, focusing on education, social life, economy, environment, and religious experience. Using a qualitative descriptive method, data were collected via observation, interviews, and documentation. Results show, Quran training and Children's Islamic Festival improved children's religious literacy, social skills, and confidence; KKN strengthened togetherness, solidarity, and tolerance through religious moderation; digitalizing MSMEs using Google Maps expanded market access, improved digital literacy, and supported local growth; the program raised awareness of cleanliness and public space preservation; and moderation values fostered an inclusive, tolerant, and harmonious community. KKN is a strategic instrument for sustainable village development. Students are implementers and agents of change bridging academic knowledge with community needs, benefiting both community and students.